2011
DOI: 10.1107/s1600536811007781
|View full text |Cite
|
Sign up to set email alerts
|

(2E)-3-(3,4-Dimethoxyphenyl)-1-(4-hydroxyphenyl)prop-2-en-1-one

Abstract: In the title compound, C17H16O4, the dihedral angle between the mean planes of the hy­droxy­phenyl and dimeth­oxy­phenyl rings is 19.34 (7)°. The mean plane of the prop-2-en-1-one group, the active site in this mol­ecule, makes angles of 7.40 (8) and 13.25 (8)°, respectively, with the hy­droxy­phenyl and dimeth­oxy­phenyl rings. The crystal packing is stabilized by O—H⋯O hydrogen bonds, weak inter­molecular C—H⋯O and π–π stacking inter­actions [centroid–centroid distance = 3.7386 (9) Å].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The bond lengths (Allen et al, 1987) and bond angles are within normal values. The bond angles C6-C7-C8 = 119.12 (14) ° and C8═C9-C10 = 127.20 (17) ° are comparable with those in a similar reported structure (E)-3- (Jasinski et al, 2011). This may be due to the presence of the keto group and associated steric forces.…”
Section: S1 Commentsupporting
confidence: 82%
See 1 more Smart Citation
“…The bond lengths (Allen et al, 1987) and bond angles are within normal values. The bond angles C6-C7-C8 = 119.12 (14) ° and C8═C9-C10 = 127.20 (17) ° are comparable with those in a similar reported structure (E)-3- (Jasinski et al, 2011). This may be due to the presence of the keto group and associated steric forces.…”
Section: S1 Commentsupporting
confidence: 82%
“…For the biological activity of chalcones and chalcone derivatives, see: Marais et al (2005); Di Carlo et al (1999);Troeberg et al (2000); Ni et al (2004). For a related structure, see: Jasinski et al (2011). For the synthesis, see: Sidharthan et al (2012); Chitra et al (2013).…”
Section: Related Literaturementioning
confidence: 99%
“…For general background and applications of chalcones, see: Awad et al (1960); Coudert et al (1988); Insuasty et al (1992Insuasty et al ( , 1997; Kolos et al (1996); Sarojini et al (2006); Shettigar et al (2010); Samshuddin et al (2010); Fun et al (2010). For related structures, see: Butcher et al (2006); Ravishankar et al (2003Ravishankar et al ( , 2005; Narayana et al (2007); Sarojini, Narayana et al (2007); ; Sharma et al (1997); Jasinski et al (2011). For hydrogen-bond motifs, see: Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…Chalcones are also finding application as organic nonlinear optical materials (NLO) for their SHG conversion efficiency (Sarojini et al, 2006;Shettigar et al, 2010). The crystal structures of some of the related chalcones viz 1-(3,4-dimethoxyphenyl)-3-(3-methylphenyl)prop-2-en-1-one (Sharma et al, 1997), 3-(3,4-dimethoxyphenyl)-1-(4-hydroxy-phenyl)prop-2-en-1-one (Ravishankar et al, 2003), 1-(4chlorophenyl)-3-(4-hydroxyphenyl) prop-2-en-1-one (Ravishankar et al, 2005) (Sarojini, Narayana et al, 2007; and 2E (Jasinski et al, 2011) have been reported. In continuation to our studies on structures of chalcones, we report here the crystal structure of a new chalcone, the title compound.…”
Section: S1 Commentmentioning
confidence: 99%
“…The product was precipitated and dried, and recrystallized by the rectified spirit to get 3‐(3,4‐dimethoxyphenyl)‐1‐(4‐hydroxyphenyl)prop‐2‐en‐1‐one ( 3 ). [ 24 ]…”
Section: Methodsmentioning
confidence: 99%